2010
DOI: 10.1097/meg.0b013e328336ec6e
|View full text |Cite
|
Sign up to set email alerts
|

Listening to music does not reduce pain during sigmoidoscopy

Abstract: Listening to music by patients did not reduce pain intensity during sigmoidoscopy. As a consequence, music during sigmoidoscopy is not recommended for this purpose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0
7

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 12 publications
2
13
0
7
Order By: Relevance
“…Records were excluded if they were deemed irrelevant or not related to the study. On further scrutiny, 4 studies[5,6,15,22] reported on outcomes after music during flexible sigmoidoscopy in respect to anxiety, pain scores and whether it was deemed helpful. These studies were chosen based on our inclusion criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Records were excluded if they were deemed irrelevant or not related to the study. On further scrutiny, 4 studies[5,6,15,22] reported on outcomes after music during flexible sigmoidoscopy in respect to anxiety, pain scores and whether it was deemed helpful. These studies were chosen based on our inclusion criteria (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…All 4 studies[5,6,15,22] were published in English. Three studies were carried out in the United States[5,6,15] and one[22] in Europe. All studies were comparative, 3 used randomized allocation, but no blinding.…”
Section: Resultsmentioning
confidence: 99%
“…A musicoterapia tem sido cada vez mais utilizada em diferentes modalidades, desde pacientes com doenças neurológicas no tratamento intensivo e na medicina paliativa (Good et al, 1999;Meeuse et al, 2010;Trappe, 2011). Em odontologia não foi possível encontrar nenhuma pesquisa clínica randomizada, controlada, casocontrole que empregasse a musicoterapia, propriamente dita, para o controle das reações decorrentes da ansiedade.…”
Section: Discussionunclassified
“…Terapêutica ansiolítica baseada na música é uma intervenção barata, pois se resume inicialmente a aquisição do equipamento tocador de música e aos fones de ouvido que reduzem grande porcentagem dos ruídos externos (Evans, 2002;Meeuse et al, 2010;Vaajoki et al, 2011).…”
Section: Música Como Agente Terapêutico Anti-estresseunclassified
See 1 more Smart Citation